1989
DOI: 10.1159/000125133
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Coexistence of Corticotropin-Releasing Factor-, Neurotensin-, Enkephalin-, Cholecystokinin-, Galanin- and Vasoactive Intestinal Polypeptide/Peptide Histidine Isoleucine-Like Peptides in the Parvocellular Part of the Paraventricular Nucleus

Abstract: The distribution of several peptides, corticotropin-releasing factor (CRF), neurotensin (NT), enkephalin (ENK), vasoactive intestinal polypeptide (VIP), peptide histidine isoleucine (PHI), cholecystokinin (CCK), thyrotropin-releasing hormone (TRH) and galanin (GAL) was studied in detail with immunohistochemistry in the various subdivisions of the parvocellular part of the rat hypothalamic paraventricular nucleus (PVN). Using a double-staining method and elution-restaining technique, the coexistence of CRF- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
81
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(94 citation statements)
references
References 35 publications
11
81
2
Order By: Relevance
“…Other hypothalamically abundant neuropeptides such as corticotrophin-releasing factor (52) and arginine vasopressin (53) have also been implicated in mood regulation. Double immunolabeling studies have showed that whereas the coexistence between corticotrophin-releasing factor and galanin is very low (54), the coexistence between arginine vasopressin and galanin is very common in the paraventricular nucleus (55), and it has been shown that the arginine vasopressin release can be regulated by galanin (56). On the other hand, a recent study showed that REM sleep deprivation selectively up-regulates galanin expression without affecting the mRNA levels of either corticotrophin-releasing factor or arginine vasopressin (51), suggesting that a galaninergic antidepressant-like effect might be achieved without the influence of these additional neuropeptide systems.…”
Section: Discussionmentioning
confidence: 99%
“…Other hypothalamically abundant neuropeptides such as corticotrophin-releasing factor (52) and arginine vasopressin (53) have also been implicated in mood regulation. Double immunolabeling studies have showed that whereas the coexistence between corticotrophin-releasing factor and galanin is very low (54), the coexistence between arginine vasopressin and galanin is very common in the paraventricular nucleus (55), and it has been shown that the arginine vasopressin release can be regulated by galanin (56). On the other hand, a recent study showed that REM sleep deprivation selectively up-regulates galanin expression without affecting the mRNA levels of either corticotrophin-releasing factor or arginine vasopressin (51), suggesting that a galaninergic antidepressant-like effect might be achieved without the influence of these additional neuropeptide systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the central nervous system, Vip expression is found in the suprachiasmatic nucleus and the paraventricular nucleus of the hypothalamus, where it influences circadian clocks and pituitary adrenocorticotropic hormone secretion, respectively (Ceccatelli et al, 1989;Hökfelt et al, 1987;Nussdorfer and Malendowicz, 1998;Vosko et al, 2007). Although Vip immunoreactivity and Vip binding sites have been found in the mammillary nuclei (Saper, 2000;Sarrieau et al, 1994), VIP expression itself in the MA is not reported in the mouse expression atlas, suggesting that the expression of Vip in this region in zebrafish might not be an evolutionarily conserved feature.…”
Section: Evolutionary Conservation Of the Vip-and Uts1-positive Neuromentioning
confidence: 99%
“…It is specifically involved in the initiation of parturition and milk ejection, and is itself a stimulator of PRL secretion (see below) (Samson et al, 1986). VIP, also a major mediator of PRL secretion, is found in cells of the parvocellular PVN (see below) (Ceccatelli et al, 1989). The SON, which has developmental and cellular similarities to the PVN, contains OT-positive cells (Saper, 1990;Van de Kar et al, 1995).…”
Section: Hypothalamusmentioning
confidence: 99%